Effects of triiodobenzoic acid on growth, yield and photosynthetic pigmentcontent of chickpea (cicer arietinum l.) (Bangladesh Journal of Botany, 2024)
An experiment was conducted to evaluate the effect of seed soaking treatment of TIBA (10, 15, 20, 25, 30 and 35 ppm) on growth, yield and photosynthetic pigment content of chickpea var. BARI Chhola-6. Results revealed that TIBA had mostly retarding effects on plant height of BARI Chhola-6 with both significant and non-significant variations. The Number of branches and leaves per plant was positively influenced following all concentrations of TIBA where, seed treated with 35 ppm TIBA produced the highest values. Results revealed that TIBA treatments had inducing effects on flower initiation and completion. Application of TIBA induced the yield and yield attributes of BARI Chhola-6 where, 30 ppm TIBA produced the highest number of pods (72.25), maximum number of seeds per plant (112.13), 100-seed weight (23.84g) and yield per plant (15.92g). TIBA had pronounced effects on the photosynthetic pigment content of BARI Chhola-6 although 35 ppm TIBA resulted maximum values but not significantly different from 30 ppm and some other treatments. Of seven treatmnts, 30 ppm TIBA produced better stimulations.Bangladesh J. Bot. 53(4): 949-955, 2024 (December)